A kind of nano zinc oxide modified flame retardant antibacterial polyester fiber and preparation method thereof
Through nano zinc oxide-cellulose nanocrystal modified polyester fibers, combined with in-situ polymerization and antioxidants, the problems of high cost and poor dispersion of flame retardant and antibacterial fibers in the prior art are solved, and low-cost and high-performance Flame retardant and antibacterial effects.
Patent Information
- Application Number
- CN202211584125.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-09
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2042-12-09
AI Technical Summary
The existing flame retardant and antibacterial polyester fibers have high cost, low yield, low fiber performance, and poor dispersion of nano zinc oxide in traditional methods, which affects flame retardant and antibacterial properties.
Using nano zinc oxide-cellulose nanocrystal modified polyester fibers, the surface modification of nano zinc oxide and cellulose nanocrystals is improved to improve its dispersion and enhancement effect in polyester, combined with oxygen resistance To reduce thermal oxygen degradation, improve flame retardant and antibacterial properties.
Low-cost, high-performance flame-retardant and antibacterial polyester fiber is realized, maintaining the mechanical properties and hue of the fiber, expanding the application field, and avoiding the complexity and high cost problems in traditional methods.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of flame-retardant antibacterial polyester fibers, in particular to a nano zinc oxide modified flame-retardant antibacterial polyester fiber and a preparation method thereof. Background Art
[0002] Polyethylene terephthalate (PET) is the world's largest fiber-forming polymer with the widest range of uses. Polyester fibers are widely used in the fields of civil and industrial fabrics. Therefore, in view of the major challenges facing the current human living environment, it is necessary to further develop antibacterial and flame-retardant polyester fibers with high safety and protection properties, promote industrial upgrading, and meet the application of fiber materials and textiles in more diverse fields such as fire protection, outdoor equipment, and medical protection.
[0003] At present, the traditional flame retardant antibacterial polyester fiber, for example, the Chinese invention patent with the publication number CN 111748084 A discloses an antibacterial flame retardant polyester resin and its preparation method, wherein a halogen-free copolymerized phosphorus flame retardant, ethylene glycol and a composite catalyst are reacted to obtain a phosphorus flame retardant esterification liquid; nano zinc oxide, ethylene glycol and a surfactant are ground to obtain a nano zinc oxide / ethylene glycol slurry; terephthalic acid and ethylene glycol are added to a reactor for esterification reaction, and then the phosphorus flame retardant esterification liquid, nano zinc oxide / ethylene glycol slurry, a thermal stabilizer and a polycondensation catalyst are added for polycondensation reaction, and then cooled and pelletized to obtain an antibacterial flame retardant polyester resin. This patent mainly uses phosphorus flame retardants and silver or zinc antibacterial agents, which have high costs, low yields and low fiber performance.
[0004] Cellulose is the most abundant organic renewable material on earth, with excellent mechanical properties, good chemical stability and high thermal stability. It is reported that under low heating rate and low temperature exposure conditions, cellulose will undergo dehydration reaction, and the rearrangement of cellulose will lead to carbonization, and the carbonized layer formed has a good flame retardant effect. Compared with the method of adding traditional flame retardants to polyester fibers for preparation, the addition of cellulose does not damage the original properties of the fiber, but also makes the polyester fiber have good flame retardant properties. In addition, nano zinc oxide has a strong inhibitory or killing effect on pathogenic bacteria such as Escherichia coli, Staphylococcus aureus, and Salmonella, and nano zinc oxide, as a new type of zinc source, has high biological activity, good immunomodulatory ability and high absorption rate while having selective toxicity and good biocompatibility. Therefore, combining cellulose with nano zinc oxide can make polyester fibers have good flame retardant and antibacterial properties at the same time, improve the product performance of the fiber, and expand its application field. Summary of the invention
[0005] In order to solve the above technical problems, the present invention provides a nano zinc oxide modified flame retardant and antibacterial polyester fiber and a preparation method thereof. By adding nano zinc oxide-cellulose nanocrystals, the polyester fiber has good flame retardant and antibacterial properties, thereby improving the product performance of the fiber and expanding its application field.
[0006] The purpose of the present invention is achieved through the following technical solutions:
[0007] In the first aspect, the present invention provides a nano zinc oxide modified flame retardant antibacterial polyester fiber, the raw materials of the polyester fiber comprising: purified terephthalic acid, ethylene glycol, nano zinc oxide-cellulose nanocrystals, an antioxidant and a catalyst; the addition amount of the nano zinc oxide-cellulose nanocrystals accounts for 5000 to 10000 ppm of the polyester fiber mass.
[0008] The present invention adopts nano zinc oxide-cellulose nanocrystals to make the polyester fiber have both antibacterial properties and flame retardant properties. Compared with traditional flame retardant antibacterial agents, it is low in price, environmentally safe and has high surface activity, and can obtain multifunctional polyester fibers with a wider range of applications.
[0009] During the heating process, cellulose will thermally decompose and carbonize. Using nano zinc oxide (ZnO) to treat cellulose materials can provide UV protection and enhance flame retardancy. Specifically, nano zinc oxide will promote the formation of carbon during the combustion process. Metal ions affect the thermal decomposition and pyrolysis behavior of cellulose by reducing the production of levoglucosan and increasing the production of carbon, water, and low molecular weight compounds, thereby further enhancing the flame retardant effect. At the same time, nano zinc oxide can exhibit excellent antibacterial properties, thus having a synergistic effect with cellulose to achieve flame retardant and antibacterial effects. In addition, the addition amount of nano zinc oxide-cellulose nanocrystals is particularly important for the other properties of polyester fibers. When controlled within this range, the mechanical properties and hue of polyester fibers can be maintained at a high level while having good flame retardant and antibacterial properties.
[0010] Preferably, the length of the cellulose nanocrystal is no more than 500 nm, the diameter is no more than 50 nm, and the aspect ratio L / D is 10-15.
[0011] Preferably, the particle size of the nano zinc oxide is less than 1 μm.
[0012] In addition, nanomaterials have surface effects, size effects, tunneling effects, etc., but their surface activity is too high and they are prone to agglomeration. If the size of cellulose nanocrystals and nano zinc oxide is too small, the surface energy is relatively large and it is easy to agglomerate, resulting in poor dispersion, affecting the modification effect of cellulose nanocrystals on the surface of nano zinc oxide, and affecting subsequent spinning and fiber mechanical properties; if the size is too large, the specific surface area is small, the activity is low, and the nano effect is difficult to play, resulting in reduced fiber flame retardancy, so it is necessary to choose the right size.
[0013] Preferably, the molar ratio of purified terephthalic acid to ethylene glycol is 1:1.1-1.5.
[0014] In a second aspect, the present invention also provides a method for preparing a nano zinc oxide modified flame retardant antibacterial polyester fiber, comprising the following steps:
[0015] (1) adding a methanol solution of sodium hydroxide dropwise to a methanol solution of zinc acetate while stirring, stopping stirring after the dropwise addition is completed, and heating for reaction; then stopping heating and continuing stirring to obtain a nano zinc oxide sol;
[0016] (2) mixing the nano zinc oxide sol and the aqueous suspension of cellulose nanocrystals, and then drying and grinding to obtain nano zinc oxide-cellulose nanocrystals; adding the nano zinc oxide-cellulose nanocrystals and the dispersant into ethylene glycol and stirring and dispersing them to obtain a nano zinc oxide-cellulose nanocrystal ethylene glycol dispersion;
[0017] (3) Purified terephthalic acid, ethylene glycol, ZnO-cellulose nanocrystal ethylene glycol dispersion, antioxidant and catalyst are mixed and pulped, and the pulped product is subjected to a first esterification reaction, a second esterification reaction, a pre-polycondensation reaction and a final polycondensation reaction in sequence, and the obtained polyester melt is sliced and melt-spun to obtain a flame-retardant and antibacterial polyester fiber.
[0018] The present invention adopts an in-situ polymerization method to prepare flame-retardant antibacterial polyester, avoiding the disadvantages of the traditional method of using nano zinc oxide antibacterial masterbatch blending, such as complex preparation of antibacterial masterbatch, high pollution, high cost and poor dispersibility of nano zinc oxide. After the nano zinc oxide is modified by cellulose nanocrystals, the steric hindrance on the surface of nano zinc oxide can be increased and the surface energy can be reduced, thereby improving the dispersibility of nano zinc oxide in ethylene glycol. At the same time, an antioxidant is introduced in the polymerization process to inhibit the thermal oxidation degradation of zinc oxide, reduce the viscosity drop in the melt spinning process, and improve the strength of the fiber.
[0019] In addition, in the traditional method, nano zinc oxide and fiber nanocrystals are simply physically mixed and modified, and the interface contact between the two is not very tight, and they are easily separated, and the synergistic effect is weak. The nano zinc oxide-cellulose nanocrystals in the present invention are obtained by modifying nano zinc oxide with cellulose nanocrystals. The modification and combination of the two are affected by controlling the reaction raw material ratio and the preparation steps. Compared with the simple physical mixing of nano zinc oxide and cellulose nanocrystals, the interface contact between the two is very tight, and the coordination effect is more obvious. Nano zinc oxide promotes the formation of cellulose carbon layer better, and the carbon layer is more densely modified on the surface of nano zinc oxide, and thus the flame retardant effect is better. In addition, the dispersion and fiber reinforcement obtained by modifying nano zinc oxide with cellulose nanocrystals are better, and the spinnability after adding it to polyester fiber is better. While improving the flame retardant and antibacterial properties, the polyester fiber can also maintain good mechanical properties and color.
[0020] Preferably, in step (1), the heating reaction is heated to 50-60° C. and maintained for 30-40 min; the mass concentration of the methanol solution of sodium hydroxide is 2-5%; and the mass concentration of the methanol solution of zinc acetate is 5-10%.
[0021] Preferably, in step (2), the mass concentration of the aqueous suspension of cellulose nanocrystals is 2-5%; the mass ratio of the nano zinc oxide sol to the aqueous suspension of cellulose nanocrystals is 1:0.5-2; the dispersant is one of polyvinyl pyrrolidone, sodium polyacrylate and sodium hexametaphosphate, and its added amount accounts for 0.5-2% of the mass of nano zinc oxide-cellulose nanocrystals; the mass concentration of nano zinc oxide-cellulose nanocrystals in the nano zinc oxide-cellulose nanocrystal ethylene glycol dispersion is 10-50%.
[0022] The modification ratio of cellulose nanocrystals on the surface of nano-zinc oxide will affect the spinnability of the fiber after it is added into the fiber, as well as the mechanical properties and hue of the fiber. The overall performance of the fiber is better under this condition range.
[0023] Preferably, in step (3), the antioxidant is one of antioxidant 1010, antioxidant 1076 and antioxidant 168, and its addition amount accounts for 300 to 1000 ppm of the mass of the polyester fiber; the catalyst is antimony glycol or antimony trioxide, and its addition amount accounts for 50 to 300 ppm of the mass of the polyester fiber;
[0024] Preferably, in step (3), the beating temperature is 60-120°C, and the beating time is 2-6h; the pressure of the first esterification reaction is 100-400KPa, the temperature is 245-250°C, and the time is 60-90min; the mass of the esterification by-products collected from the first esterification reaction reaches 85-95% of the theoretical value, and the product after the first esterification reaction is subjected to a second esterification reaction, and the temperature of the second esterification reaction is 250-260°C, and the time is 30-60min.
[0025] Preferably, in step (3), the mass of the esterification by-products collected from the second esterification reaction is greater than 95% of the theoretical value, and the product after the second esterification reaction is subjected to a pre-polycondensation reaction, wherein the pressure of the pre-polycondensation reaction is 150-500 Pa, the temperature is 260-270° C., and the time is 50-70 min; the pressure of the final polycondensation reaction is 150-200 Pa, the temperature is 270-275° C., and the time is 30-120 min; and the process parameters of the melt spinning are: spinning box temperature 278-285° C., cooling air temperature 20-25° C., oiling rate 0.42-1.5wt%, and winding speed 4000-4600 m / min.
[0026] In addition, the final shrinkage temperature is controlled at 270-275°C to reduce the side effects of thermal degradation catalyzed by zinc oxide and improve the hue of the polyester melt.
[0027] Compared with the prior art, the present invention has the following beneficial effects:
[0028] (1) Surface modification of zinc oxide with cellulose nanocrystals can not only promote the carbonization of cellulose nanocrystals during combustion, thereby improving flame retardancy, but also improve the dispersibility and reinforcement of the polyester fibers, thereby improving the spinnability of the fibers. While improving the flame retardancy and antibacterial properties of the polyester fibers, the polyester fibers can also maintain good mechanical properties and color.
[0029] (2) By in-situ polymerization, nano zinc oxide modified with cellulose nanocrystals is introduced into the polymerization process, which effectively improves its dispersibility in polyester, avoids the shortcomings of the traditional method of using nano zinc oxide antibacterial masterbatch blending, such as complex preparation of antibacterial masterbatch, high pollution and high cost, and poor dispersibility of nano zinc oxide, and greatly reduces the cost;
[0030] (3) Introducing antioxidants and lowering the final polycondensation temperature during the in-situ polymerization process can effectively reduce the catalytic thermal degradation of nano-zinc oxide, avoid the problem of yellowing of polyester, and improve product quality. DETAILED DESCRIPTION
[0031] The technical solution of the present invention is described below with specific embodiments, but the protection scope of the present invention is not limited thereto:
[0032] Example 1
[0033] A method for preparing nano zinc oxide modified flame retardant antibacterial polyester fiber comprises the following steps:
[0034] (1) Add 5 g of anhydrous zinc acetate to 50 mL of methanol, heat the solution to 50°C and stir for 30 min to obtain a methanol solution of zinc acetate; add 3 g of sodium hydroxide to 50 mL of methanol, heat the solution to 50°C and stir for 60 min to obtain a methanol solution of sodium hydroxide. Then, under continuous stirring for 30 min, add the methanol solution of sodium hydroxide dropwise to the methanol solution of zinc acetate, stop stirring, keep at 50°C for 30 min, then stop heating, and stir for another 2 h to form a nano zinc oxide sol.
[0035] (2) Cellulose nanocrystals (average length of 400 nm, average diameter of 40 nm, aspect ratio L / D of 10) were added to deionized water and stirred, and then ultrasonicated until the solution was stable and clear, to obtain a cellulose nanocrystal aqueous suspension with a mass concentration of 4%. Next, nano zinc oxide sol and cellulose nanocrystal aqueous suspension were mixed in a mass ratio of 1:1, stirred evenly, and then the mixture was placed in an oven at 80°C to dry until all the solvent evaporated; finally, the dried mixture was ground into fine powder to obtain nano zinc oxide-cellulose nanocrystals.
[0036] Nano zinc oxide-cellulose nanocrystals and polyvinyl pyrrolidone are added into ethylene glycol for stirring and dispersion, wherein the amount of polyvinyl pyrrolidone added is 1% of the mass of the nano zinc oxide-cellulose nanocrystals. The nano zinc oxide-cellulose nanocrystals are then transferred into a sand mill for cyclic grinding to obtain a nano zinc oxide-cellulose nanocrystal ethylene glycol dispersion with a solid content of 10%, wherein the particle size of the nano zinc oxide in the dispersion is less than 1 μm.
[0037] (3) adding purified terephthalic acid, ethylene glycol, nano zinc oxide-cellulose nanocrystal ethylene glycol dispersion, antioxidant 1010 and ethylene glycol antimony to a beating kettle for beating, wherein the molar ratio of terephthalic acid to ethylene glycol is 1:1.2, the amount of nano zinc oxide-cellulose nanocrystal added is 6000 ppm by weight of the polyester, the amount of antioxidant 1010 added is 500 ppm by weight of the polyester, the amount of ethylene glycol antimony added is 100 ppm by weight of the polyester, the beating temperature is 70°C, and the beating time is 2 h;
[0038] The pulped product is subjected to a first esterification reaction at a pressure of 300 KPa, a temperature of 250° C., and a time of 90 min. When the mass of the esterification byproducts collected from the first esterification reaction reaches 90±2% of the theoretical value, the product after the first esterification reaction is subjected to a second esterification reaction at a temperature of 260° C. and a time of 60 min. When the mass of the esterification byproducts collected from the second esterification reaction is greater than 95% of the theoretical value, the product after the second esterification reaction is subjected to a pre-polycondensation reaction to obtain a pre-polycondensation product at a pressure of 350 Pa. The temperature is 270°C and the time is 60 minutes; the product after the pre-polycondensation is evacuated to a high vacuum and then subjected to a final polycondensation reaction at a pressure of 150 Pa, a temperature of 273°C and a time of 90 minutes to obtain a polyester melt; the polyester melt is discharged, cooled and pelletized to obtain nano zinc oxide modified flame retardant and antibacterial polyester chips; the chips are melt-spun, the spinning box temperature is 282°C, the number of spinneret holes is 72, the cooling air temperature is 22°C, the oiling rate is 1.0wt%, and the winding speed is 4200m / min to obtain flame retardant and antibacterial polyester fibers.
[0039] Example 2
[0040] A method for preparing nano zinc oxide modified flame retardant antibacterial polyester fiber comprises the following steps:
[0041] (1) Add 5 g of anhydrous zinc acetate to 50 mL of methanol, heat the solution to 50°C and stir for 30 min to obtain a methanol solution of zinc acetate; add 3 g of sodium hydroxide to 50 mL of methanol, heat the solution to 50°C and stir for 60 min to obtain a methanol solution of sodium hydroxide. Then, under continuous stirring for 30 min, add the methanol solution of sodium hydroxide dropwise to the methanol solution of zinc acetate, stop stirring, keep at 50°C for 30 min, then stop heating, and stir for another 2 h to form a nano zinc oxide sol.
[0042] (2) Cellulose nanocrystals (average length of 420 nm, average diameter of 35 nm, aspect ratio L / D of 10) were added to deionized water and stirred, and then ultrasonicated until the solution was stable and clear, to obtain a cellulose nanocrystal aqueous suspension with a mass concentration of 4%. Next, nano zinc oxide sol and cellulose nanocrystal aqueous suspension were mixed in a mass ratio of 1:1, stirred evenly, and then the mixture was placed in an oven at 80°C to dry until all the solvent evaporated; finally, the dried mixture was ground into fine powder to obtain nano zinc oxide-cellulose nanocrystals.
[0043] Nano zinc oxide-cellulose nanocrystals and polyvinyl pyrrolidone are added into ethylene glycol for stirring and dispersion, wherein the amount of polyvinyl pyrrolidone added is 1% of the mass of the nano zinc oxide-cellulose nanocrystals. The nano zinc oxide-cellulose nanocrystals are then transferred into a sand mill for cyclic grinding to obtain a nano zinc oxide-cellulose nanocrystal ethylene glycol dispersion with a solid content of 15%, wherein the particle size of the nano zinc oxide in the dispersion is less than 1 μm.
[0044] (3) adding purified terephthalic acid, ethylene glycol, nano zinc oxide-cellulose nanocrystal ethylene glycol dispersion, antioxidant 1010 and ethylene glycol antimony to a beating kettle for beating, wherein the molar ratio of terephthalic acid to ethylene glycol is 1:1.2, the amount of nano zinc oxide-cellulose nanocrystal added is 7000 ppm by weight of the polyester, the amount of antioxidant 1010 added is 500 ppm by weight of the polyester, the amount of ethylene glycol antimony added is 100 ppm by weight of the polyester, the beating temperature is 70°C, and the beating time is 2 h;
[0045] The pulped product is subjected to a first esterification reaction at a pressure of 300 KPa, a temperature of 250° C., and a time of 90 min. When the mass of the esterification byproducts collected from the first esterification reaction reaches 90±2% of the theoretical value, the product after the first esterification reaction is subjected to a second esterification reaction at a temperature of 260° C. and a time of 60 min. When the mass of the esterification byproducts collected from the second esterification reaction is greater than 95% of the theoretical value, the product after the second esterification reaction is subjected to a pre-polycondensation reaction to obtain a pre-polycondensation product at a pressure of 350 Pa. The temperature is 270°C and the time is 60 minutes; the product after the pre-polycondensation is evacuated to a high vacuum and then subjected to a final polycondensation reaction at a pressure of 150 Pa, a temperature of 274°C and a time of 90 minutes to obtain a polyester melt; the polyester melt is discharged, cooled and pelletized to obtain nano zinc oxide modified flame retardant and antibacterial polyester chips; the chips are melt-spun, the spinning box temperature is 282°C, the number of spinneret holes is 72, the cooling air temperature is 22°C, the oiling rate is 1.0wt%, and the winding speed is 4200m / min to obtain flame retardant and antibacterial polyester fibers.
[0046] Example 3
[0047] A method for preparing nano zinc oxide modified flame retardant antibacterial polyester fiber comprises the following steps:
[0048] (1) Add 5 g of anhydrous zinc acetate to 50 mL of methanol, heat the solution to 50°C and stir for 30 min to obtain a methanol solution of zinc acetate; add 3 g of sodium hydroxide to 50 mL of methanol, heat the solution to 50°C and stir for 60 min to obtain a methanol solution of sodium hydroxide. Then, under continuous stirring for 30 min, add the methanol solution of sodium hydroxide dropwise to the methanol solution of zinc acetate, stop stirring, keep at 50°C for 30 min, then stop heating, and stir for another 2 h to form a nano zinc oxide sol.
[0049] (2) Cellulose nanocrystals (average length of 450 nm, average diameter of 30 nm, aspect ratio L / D of 10) were added to deionized water and stirred, and then ultrasonicated until the solution was stable and clear, to obtain a cellulose nanocrystal aqueous suspension with a mass concentration of 4%. Next, nano zinc oxide sol and cellulose nanocrystal aqueous suspension were mixed in a mass ratio of 1:1, stirred evenly, and then the mixture was placed in an oven at 80°C to dry until all the solvent evaporated; finally, the dried mixture was ground into fine powder to obtain nano zinc oxide-cellulose nanocrystals.
[0050] Nano zinc oxide-cellulose nanocrystals and polyvinyl pyrrolidone are added to ethylene glycol for stirring and dispersion, wherein the amount of polyvinyl pyrrolidone added is 1% of the mass of the nano zinc oxide-cellulose nanocrystals. The nano zinc oxide-cellulose nanocrystals are then transferred to a sand mill for cyclic grinding to obtain a nano zinc oxide-cellulose nanocrystal ethylene glycol dispersion with a solid content of 20%, wherein the particle size of the nano zinc oxide in the dispersion is less than 1 μm.
[0051] (3) adding purified terephthalic acid, ethylene glycol, nano zinc oxide-cellulose nanocrystal ethylene glycol dispersion, antioxidant 1010 and ethylene glycol antimony to a pulping kettle for pulping, wherein the molar ratio of terephthalic acid to ethylene glycol is 1:1.2, the amount of nano zinc oxide-cellulose nanocrystal added is 8000 ppm by weight of the polyester, the amount of antioxidant 1010 added is 500 ppm by weight of the polyester, the amount of ethylene glycol antimony added is 100 ppm by weight of the polyester, the pulping temperature is 70°C, and the pulping time is 2 h;
[0052] The pulped product is subjected to a first esterification reaction at a pressure of 300 KPa, a temperature of 250° C., and a time of 90 min. When the mass of the esterification byproducts collected from the first esterification reaction reaches 90±2% of the theoretical value, the product after the first esterification reaction is subjected to a second esterification reaction at a temperature of 260° C. and a time of 60 min. When the mass of the esterification byproducts collected from the second esterification reaction is greater than 95% of the theoretical value, the product after the second esterification reaction is subjected to a pre-polycondensation reaction to obtain a pre-polycondensation product at a pressure of 350 Pa. The temperature is 270°C and the time is 60 minutes; the product after the pre-polycondensation is subjected to high vacuum and then subjected to final polycondensation reaction, the pressure is 150Pa, the temperature is 275°C, and the time is 90 minutes to obtain a polyester melt; the polyester melt is discharged, cooled, and pelletized to obtain nano zinc oxide modified flame retardant and antibacterial polyester chips; the chips are melt-spun, the spinning box temperature is 282°C, the number of spinneret holes is 72, the cooling air temperature is 22°C, the oiling rate is 1.0wt%, and the winding speed is 4200m / min to obtain flame retardant and antibacterial polyester fibers.
[0053] Comparative Example 1
[0054] The difference from Example 1 is that the nano zinc oxide is not modified with cellulose nanocrystals.
[0055] A method for preparing nano zinc oxide modified flame retardant antibacterial polyester fiber comprises the following steps:
[0056] (1) Adding nano zinc oxide and polyvinyl pyrrolidone into ethylene glycol for stirring and dispersion, wherein the amount of polyvinyl pyrrolidone added is 1% of the mass of the nano zinc oxide, and then transferring to a sand mill for cyclic grinding to obtain a nano zinc oxide ethylene glycol dispersion with a solid content of 10%, wherein the particle size of the nano zinc oxide in the dispersion is less than 1 μm.
[0057] (2) adding purified terephthalic acid, ethylene glycol, nano zinc oxide ethylene glycol dispersion, antioxidant 1010 and ethylene glycol antimony to a beating kettle for beating, wherein the molar ratio of terephthalic acid to ethylene glycol is 1:1.2, the amount of nano zinc oxide added is 6000 ppm by weight of the polyester, the amount of antioxidant 1010 added is 500 ppm by weight of the polyester, the amount of ethylene glycol antimony added is 100 ppm by weight of the polyester, the beating temperature is 70° C., and the beating time is 2 h;
[0058] The pulped product is subjected to a first esterification reaction at a pressure of 300 KPa, a temperature of 250° C., and a time of 90 min. When the mass of the esterification byproducts collected from the first esterification reaction reaches 90±2% of the theoretical value, the product after the first esterification reaction is subjected to a second esterification reaction at a temperature of 260° C. and a time of 60 min. When the mass of the esterification byproducts collected from the second esterification reaction is greater than 95% of the theoretical value, the product after the second esterification reaction is subjected to a pre-polycondensation reaction to obtain a pre-polycondensation product at a pressure of 350 Pa. The temperature is 270°C and the time is 60 minutes; the product after the pre-polycondensation is evacuated to a high vacuum and then subjected to a final polycondensation reaction at a pressure of 150 Pa, a temperature of 273°C and a time of 90 minutes to obtain a polyester melt; the polyester melt is discharged, cooled and pelletized to obtain nano zinc oxide modified flame retardant and antibacterial polyester chips; the chips are melt-spun, the spinning box temperature is 282°C, the number of spinneret holes is 72, the cooling air temperature is 22°C, the oiling rate is 1.0wt%, and the winding speed is 4200m / min to obtain flame retardant and antibacterial polyester fibers.
[0059] Comparative Example 2
[0060] The difference from Example 1 is that no antioxidant is added.
[0061] A method for preparing nano zinc oxide modified flame retardant antibacterial polyester fiber comprises the following steps:
[0062] (1) Add 5 g of anhydrous zinc acetate to 50 mL of methanol, heat the solution to 50°C and stir for 30 min to obtain a methanol solution of zinc acetate; add 3 g of sodium hydroxide to 50 mL of methanol, heat the solution to 50°C and stir for 60 min to obtain a methanol solution of sodium hydroxide. Then, under continuous stirring for 30 min, add the methanol solution of sodium hydroxide dropwise to the methanol solution of zinc acetate, stop stirring, keep at 50°C for 30 min, then stop heating, and stir for another 2 h to form a nano zinc oxide sol.
[0063] (2) Cellulose nanocrystals (average length of 400 nm, average diameter of 40 nm, aspect ratio L / D of 10) were added to deionized water and stirred, and then ultrasonicated until the solution was stable and clear, to obtain a cellulose nanocrystal aqueous suspension with a mass concentration of 4%. Next, nano zinc oxide sol and cellulose nanocrystal aqueous suspension were mixed in a mass ratio of 1:1, stirred evenly, and then the mixture was placed in an oven at 80°C to dry until all the solvent evaporated; finally, the dried mixture was ground into fine powder to obtain nano zinc oxide-cellulose nanocrystals.
[0064] Nano zinc oxide-cellulose nanocrystals and polyvinyl pyrrolidone are added into ethylene glycol for stirring and dispersion, wherein the amount of polyvinyl pyrrolidone added is 1% of the mass of the nano zinc oxide-cellulose nanocrystals. The nano zinc oxide-cellulose nanocrystals are then transferred into a sand mill for cyclic grinding to obtain a nano zinc oxide-cellulose nanocrystal ethylene glycol dispersion with a solid content of 10%, wherein the particle size of the nano zinc oxide in the dispersion is less than 1 μm.
[0065] (3) adding purified terephthalic acid, ethylene glycol, nano zinc oxide-cellulose nanocrystal ethylene glycol dispersion and ethylene glycol antimony into a pulping kettle for pulping, wherein the molar ratio of terephthalic acid to ethylene glycol is 1:1.2, the amount of nano zinc oxide-cellulose nanocrystal added is 6000 ppm of the polyester mass, the amount of ethylene glycol antimony added is 100 ppm of the polyester mass, the pulping temperature is 70°C, and the pulping time is 2 h;
[0066] The pulped product is subjected to a first esterification reaction at a pressure of 300 KPa, a temperature of 250° C., and a time of 90 min. When the mass of the esterification byproducts collected from the first esterification reaction reaches 90±2% of the theoretical value, the product after the first esterification reaction is subjected to a second esterification reaction at a temperature of 260° C. and a time of 60 min. When the mass of the esterification byproducts collected from the second esterification reaction is greater than 95% of the theoretical value, the product after the second esterification reaction is subjected to a pre-polycondensation reaction to obtain a pre-polycondensation product at a pressure of 350 Pa. The temperature is 270°C and the time is 60 minutes; the product after the pre-polycondensation is evacuated to a high vacuum and then subjected to a final polycondensation reaction at a pressure of 150 Pa, a temperature of 273°C and a time of 90 minutes to obtain a polyester melt; the polyester melt is discharged, cooled and pelletized to obtain nano zinc oxide modified flame retardant and antibacterial polyester chips; the chips are melt-spun, the spinning box temperature is 282°C, the number of spinneret holes is 72, the cooling air temperature is 22°C, the oiling rate is 1.0wt%, and the winding speed is 4200m / min to obtain flame retardant and antibacterial polyester fibers.
[0067] Comparative Example 3
[0068] The difference from Example 1 is that the temperature of the final polycondensation is too high.
[0069] A method for preparing nano zinc oxide modified flame retardant antibacterial polyester fiber comprises the following steps:
[0070] (1) Add 5 g of anhydrous zinc acetate to 50 mL of methanol, heat the solution to 50°C and stir for 30 min to obtain a methanol solution of zinc acetate; add 3 g of sodium hydroxide to 50 mL of methanol, heat the solution to 50°C and stir for 60 min to obtain a methanol solution of sodium hydroxide. Then, under continuous stirring for 30 min, add the methanol solution of sodium hydroxide dropwise to the methanol solution of zinc acetate, stop stirring, keep at 50°C for 30 min, then stop heating, and stir for another 2 h to form a nano zinc oxide sol.
[0071] (2) Cellulose nanocrystals (average length of 400 nm, average diameter of 40 nm, aspect ratio L / D of 10) were added to deionized water and stirred, and then ultrasonicated until the solution was stable and clear, to obtain a cellulose nanocrystal aqueous suspension with a mass concentration of 4%. Next, nano zinc oxide sol and cellulose nanocrystal aqueous suspension were mixed in a mass ratio of 1:1, stirred evenly, and then the mixture was placed in an oven at 80°C to dry until all the solvent evaporated; finally, the dried mixture was ground into fine powder to obtain nano zinc oxide-cellulose nanocrystals.
[0072] Nano zinc oxide-cellulose nanocrystals and polyvinyl pyrrolidone are added into ethylene glycol for stirring and dispersion, wherein the amount of polyvinyl pyrrolidone added is 1% of the mass of the nano zinc oxide-cellulose nanocrystals. The nano zinc oxide-cellulose nanocrystals are then transferred into a sand mill for cyclic grinding to obtain a nano zinc oxide-cellulose nanocrystal ethylene glycol dispersion with a solid content of 10%, wherein the particle size of the nano zinc oxide in the dispersion is less than 1 μm.
[0073] (3) adding purified terephthalic acid, ethylene glycol, nano zinc oxide-cellulose nanocrystal ethylene glycol dispersion, antioxidant 1010 and ethylene glycol antimony to a beating kettle for beating, wherein the molar ratio of terephthalic acid to ethylene glycol is 1:1.2, the amount of nano zinc oxide-cellulose nanocrystal added is 6000 ppm by weight of the polyester, the amount of antioxidant 1010 added is 500 ppm by weight of the polyester, the amount of ethylene glycol antimony added is 100 ppm by weight of the polyester, the beating temperature is 70°C, and the beating time is 2 h;
[0074] The pulped product is subjected to a first esterification reaction at a pressure of 300 KPa, a temperature of 250° C., and a time of 90 min. When the mass of the esterification byproducts collected from the first esterification reaction reaches 90±2% of the theoretical value, the product after the first esterification reaction is subjected to a second esterification reaction at a temperature of 260° C. and a time of 60 min. When the mass of the esterification byproducts collected from the second esterification reaction is greater than 95% of the theoretical value, the product after the second esterification reaction is subjected to a pre-polycondensation reaction to obtain a pre-polycondensation product at a pressure of 350 Pa. The temperature is 270°C and the time is 60 minutes; the product after the pre-polycondensation is subjected to high vacuum and then subjected to final polycondensation reaction, the pressure is 150Pa, the temperature is 280°C, and the time is 90 minutes to obtain a polyester melt; the polyester melt is discharged, cooled, and pelletized to obtain nano zinc oxide modified flame retardant and antibacterial polyester chips; the chips are melt-spun, the spinning box temperature is 282°C, the number of spinneret holes is 72, the cooling air temperature is 22°C, the oiling rate is 1.0wt%, and the winding speed is 4200m / min to obtain flame retardant and antibacterial polyester fibers.
[0075] Comparative Example 4
[0076] The difference from Example 1 is that the added proportion of cellulose nanocrystals is too high.
[0077] A method for preparing nano zinc oxide modified flame retardant antibacterial polyester fiber comprises the following steps:
[0078] (1) Add 5 g of anhydrous zinc acetate to 50 mL of methanol, heat the solution to 50°C and stir for 30 min to obtain a methanol solution of zinc acetate; add 3 g of sodium hydroxide to 50 mL of methanol, heat the solution to 50°C and stir for 60 min to obtain a methanol solution of sodium hydroxide. Then, under continuous stirring for 30 min, add the methanol solution of sodium hydroxide dropwise to the methanol solution of zinc acetate, stop stirring, keep at 50°C for 30 min, then stop heating, and stir for another 2 h to form a nano zinc oxide sol.
[0079] (2) Cellulose nanocrystals (average length of 400 nm, average diameter of 40 nm, aspect ratio L / D of 10) were added to deionized water and stirred, and then ultrasonicated until the solution was stable and clear, to obtain a cellulose nanocrystal aqueous suspension with a mass concentration of 4%. Next, nano zinc oxide sol and cellulose nanocrystal aqueous suspension were mixed in a mass ratio of 1:3, stirred evenly, and then the mixture was placed in an oven at 80°C to dry until all the solvent evaporated; finally, the dried mixture was ground into fine powder to obtain nano zinc oxide-cellulose nanocrystals.
[0080] Nano zinc oxide-cellulose nanocrystals and polyvinyl pyrrolidone are added into ethylene glycol for stirring and dispersion, wherein the amount of polyvinyl pyrrolidone added is 1% of the mass of the nano zinc oxide-cellulose nanocrystals. The nano zinc oxide-cellulose nanocrystals are then transferred into a sand mill for cyclic grinding to obtain a nano zinc oxide-cellulose nanocrystal ethylene glycol dispersion with a solid content of 10%, wherein the particle size of the nano zinc oxide in the dispersion is less than 1 μm.
[0081] (3) adding purified terephthalic acid, ethylene glycol, nano zinc oxide-cellulose nanocrystal ethylene glycol dispersion, antioxidant 1010 and ethylene glycol antimony to a beating kettle for beating, wherein the molar ratio of terephthalic acid to ethylene glycol is 1:1.2, the amount of nano zinc oxide-cellulose nanocrystal added is 6000 ppm by weight of the polyester, the amount of antioxidant 1010 added is 500 ppm by weight of the polyester, the amount of ethylene glycol antimony added is 100 ppm by weight of the polyester, the beating temperature is 70°C, and the beating time is 2 h;
[0082] The pulped product is subjected to a first esterification reaction at a pressure of 300 KPa, a temperature of 250° C., and a time of 90 min. When the mass of the esterification byproducts collected from the first esterification reaction reaches 90±2% of the theoretical value, the product after the first esterification reaction is subjected to a second esterification reaction at a temperature of 260° C. and a time of 60 min. When the mass of the esterification byproducts collected from the second esterification reaction is greater than 95% of the theoretical value, the product after the second esterification reaction is subjected to a pre-polycondensation reaction to obtain a pre-polycondensation product at a pressure of 350 Pa. The temperature is 270°C and the time is 60 minutes; the product after the pre-polycondensation is evacuated to a high vacuum and then subjected to a final polycondensation reaction at a pressure of 150 Pa, a temperature of 273°C and a time of 90 minutes to obtain a polyester melt; the polyester melt is discharged, cooled and pelletized to obtain nano zinc oxide modified flame retardant and antibacterial polyester chips; the chips are melt-spun, the spinning box temperature is 282°C, the number of spinneret holes is 72, the cooling air temperature is 22°C, the oiling rate is 1.0wt%, and the winding speed is 4200m / min to obtain flame retardant and antibacterial polyester fibers.
[0083] Comparative Example 5
[0084] The difference from Example 1 is that the added amount of nano zinc oxide-cellulose nanocrystals is too much.
[0085] A method for preparing nano zinc oxide modified flame retardant antibacterial polyester fiber comprises the following steps:
[0086] (1) Add 5 g of anhydrous zinc acetate to 50 mL of methanol, heat the solution to 50°C and stir for 30 min to obtain a methanol solution of zinc acetate; add 3 g of sodium hydroxide to 50 mL of methanol, heat the solution to 50°C and stir for 60 min to obtain a methanol solution of sodium hydroxide. Then, under continuous stirring for 30 min, add the methanol solution of sodium hydroxide dropwise to the methanol solution of zinc acetate, stop stirring, keep at 50°C for 30 min, then stop heating, and stir for another 2 h to form a nano zinc oxide sol.
[0087] (2) Cellulose nanocrystals (average length of 400 nm, average diameter of 40 nm, aspect ratio L / D of 10) were added to deionized water and stirred, and then ultrasonicated until the solution was stable and clear, to obtain a cellulose nanocrystal aqueous suspension with a mass concentration of 4%. Next, nano zinc oxide sol and cellulose nanocrystal aqueous suspension were mixed in a mass ratio of 1:1, stirred evenly, and then the mixture was placed in an oven at 80°C to dry until all the solvent evaporated; finally, the dried mixture was ground into fine powder to obtain nano zinc oxide-cellulose nanocrystals.
[0088] Nano zinc oxide-cellulose nanocrystals and polyvinyl pyrrolidone are added into ethylene glycol for stirring and dispersion, wherein the amount of polyvinyl pyrrolidone added is 1% of the mass of the nano zinc oxide-cellulose nanocrystals. The nano zinc oxide-cellulose nanocrystals are then transferred into a sand mill for cyclic grinding to obtain a nano zinc oxide-cellulose nanocrystal ethylene glycol dispersion with a solid content of 10%, wherein the particle size of the nano zinc oxide in the dispersion is less than 1 μm.
[0089] (3) adding purified terephthalic acid, ethylene glycol, nano zinc oxide-cellulose nanocrystal ethylene glycol dispersion, antioxidant 1010 and ethylene glycol antimony to a pulping kettle for pulping, wherein the molar ratio of terephthalic acid to ethylene glycol is 1:1.2, the amount of nano zinc oxide-cellulose nanocrystal added is 15000 ppm by weight of the polyester, the amount of antioxidant 1010 added is 500 ppm by weight of the polyester, the amount of ethylene glycol antimony added is 100 ppm by weight of the polyester, the pulping temperature is 70°C, and the pulping time is 2 h;
[0090] The pulped product is subjected to a first esterification reaction at a pressure of 300 KPa, a temperature of 250° C., and a time of 90 min. When the mass of the esterification byproducts collected from the first esterification reaction reaches 90±2% of the theoretical value, the product after the first esterification reaction is subjected to a second esterification reaction at a temperature of 260° C. and a time of 60 min. When the mass of the esterification byproducts collected from the second esterification reaction is greater than 95% of the theoretical value, the product after the second esterification reaction is subjected to a pre-polycondensation reaction to obtain a pre-polycondensation product at a pressure of 350 Pa. The temperature is 270°C and the time is 60 minutes; the product after the pre-polycondensation is evacuated to a high vacuum and then subjected to a final polycondensation reaction at a pressure of 150 Pa, a temperature of 273°C and a time of 90 minutes to obtain a polyester melt; the polyester melt is discharged, cooled and pelletized to obtain nano zinc oxide modified flame retardant and antibacterial polyester chips; the chips are melt-spun, the spinning box temperature is 282°C, the number of spinneret holes is 72, the cooling air temperature is 22°C, the oiling rate is 1.0wt%, and the winding speed is 4200m / min to obtain flame retardant and antibacterial polyester fibers.
[0091] The properties of the flame retardant and antibacterial polyester fibers prepared in the above Examples 1-3 and Comparative Examples 1-3 were tested. The flame retardant test standard was referenced to GB / T 2406.2-2009, and the antibacterial performance test standard was referenced to GB / T 20944.3-2008. The results are shown in Table 1.
[0092] Table 1 Flame retardant and antibacterial polyester fiber performance test results
[0093]
[0094] As can be seen from Table 1, the flame retardant and antibacterial polyester fibers prepared by the method of the present invention in Examples 1-3 have good performance, a limiting oxygen index of more than 28, an antibacterial rate of more than 90%, a low hue b value, mechanical properties that meet market demand, and excellent flame retardant and antibacterial properties.
[0095] In Comparative Example 1, cellulose nanocrystals were not used to modify the surface of nano zinc oxide. The dispersibility of nano zinc oxide in the ZnO-cellulose nanocrystal ethylene glycol dispersion was poor, and the flame retardant properties of the prepared fiber were low, and the antibacterial properties were slightly reduced. This is because cellulose nanocrystals have a carbonizing effect. Without the introduction of cellulose nanocrystals, nano zinc oxide has no carbonizing effect and poor flame retardant properties. At the same time, due to the low dispersibility of nano zinc oxide, its antibacterial activity is further reduced.
[0096] It can be seen from Comparative Examples 2 and 3 that the addition of antioxidants and a slightly lower polymerization temperature can reduce the side effects of thermal degradation catalyzed by nano zinc oxide, making the fiber less prone to yellowing, reducing the hue b value, and improving product quality.
[0097] It can be seen from Comparative Example 4 that the modification ratio of cellulose nanocrystals on the surface of nano-zinc oxide is particularly important for balancing the performance of polyester fibers, and that too high a ratio of cellulose nanocrystals added will inhibit the subsequent carbonization effect and also lead to reduced flame retardant and antibacterial properties.
[0098] It can be seen from Comparative Example 5 that the addition amount of nano zinc oxide-cellulose nanocrystals is too high. Although the antibacterial performance is improved, the degradation effect is obvious, the b value becomes higher, and at the same time, the fiber stress is not concentrated, resulting in a decrease in breaking strength.
[0099] The above are only preferred embodiments of the present invention, and are not intended to limit the patent scope of the present invention. Any equivalent structure or equivalent process transformation made using the specification of the present invention, or directly or indirectly applied in other related technical fields, are also included in the patent protection scope of the present invention.
Claims
1. A method for preparing nano zinc oxide modified flame retardant antibacterial polyester fiber, It is characterized in that The steps include: (1) adding a methanol solution of sodium hydroxide dropwise to a methanol solution of zinc acetate while stirring, stopping stirring after the addition is complete, and heating for reaction; then stopping heating and continuing stirring to obtain a nano zinc oxide sol; (2) Mixing nano zinc oxide sol and cellulose nanocrystal aqueous suspension in a mass ratio of 1:0.5-2, wherein the particle size of nano zinc oxide is less than 1 μm, the length of cellulose nanocrystal is not more than 500 nm, the diameter is not more than 50 nm, the aspect ratio L / D is 10-15, and the mass concentration of cellulose nanocrystal aqueous suspension is 2-5%; then drying and grinding to obtain nano zinc oxide-cellulose nanocrystals; adding nano zinc oxide-cellulose nanocrystals and dispersant into ethylene glycol and stirring to disperse to obtain nano zinc oxide-cellulose nanocrystal ethylene glycol dispersion; (3) Purified terephthalic acid, ethylene glycol, ZnO-cellulose nanocrystal ethylene glycol dispersion, antioxidant and catalyst are mixed and beaten, and the beaten product is subjected to a first esterification reaction, a second esterification reaction, a pre-polycondensation reaction and a final polycondensation reaction in sequence, wherein the pressure of the final polycondensation reaction is 150-200 Pa, the temperature is 270-275°C, and the time is 30-120 min; the obtained polyester melt is then sliced and melt-spun to obtain a flame-retardant and antibacterial polyester fiber, and the addition amount of nano zinc oxide-cellulose nanocrystals is 5000-10000 ppm of the mass of the polyester fiber.
2. The preparation method according to claim 1, It is characterized in that In step (1), the heating reaction is heated to 50-60° C. and maintained for 30-40 min; the mass concentration of the methanol solution of sodium hydroxide is 2-5%; and the mass concentration of the methanol solution of zinc acetate is 5-10%.
3. The preparation method according to claim 1 or 2, It is characterized in that In step (2), the dispersant is one of polyvinyl pyrrolidone, sodium polyacrylate and sodium hexametaphosphate, and its added amount accounts for 0.5-2% of the mass of nano zinc oxide-cellulose nanocrystals; the mass concentration of nano zinc oxide-cellulose nanocrystals in the nano zinc oxide-cellulose nanocrystal ethylene glycol dispersion is 10-50%.
4. The preparation method according to claim 1, It is characterized in that The molar ratio of purified terephthalic acid to ethylene glycol is 1:1.1-1.
5.
5. The preparation method according to claim 1, It is characterized in that In step (3), the antioxidant is one of antioxidant 1010, antioxidant 1076 and antioxidant 168, and its added amount accounts for 300-1000 ppm of the polyester fiber mass.
6. The preparation method according to claim 1, It is characterized in that In step (3), the catalyst is antimony glycol or antimony trioxide, and the added amount thereof is 50-300 ppm based on the mass of the polyester fiber.
7. The preparation method according to claim 1, It is characterized in that In step (3), the pressure of the first esterification reaction is 100-400 KPa, the temperature is 245-250° C., and the time is 60-90 min.
8. The preparation method according to claim 1, It is characterized in that In step (3), the temperature of the second esterification reaction is 250-260° C., and the time is 30-60 min.
9. The preparation method according to claim 1 or 5 or 6 or 7 or 8, It is characterized in that In step (3), the pre-polycondensation reaction pressure is 150-500 Pa, the temperature is 260-270° C., and the time is 50-70 min; the process parameters of the melt spinning are: spinning box temperature 278-285° C., cooling air temperature 20-25° C., oil loading rate 0.42-1.5 wt %, and winding speed 4000-4600 m / min.
Citation Information
Patent Citations
Antibacterial flame-retardant polyester resin and preparation method thereof
CN111748084A
Method for manufacturing zinc oxide-cellulose nanocrystalline composite fiber film with antibacterial characteristic and photocatalytic degradation characteristic at same time
CN104018235A
Cited By
Cool antibacterial polyester fabric and preparation method thereof
CN121538757A
Cool-feeling antibacterial polyester fabric and preparation method thereof
CN121538757B
Moisture-absorbing and antibacterial polyester fiber and method for preparing the same
CN122791504A
